A global view on carbapenem-resistant Acinetobacter baumannii - Müller, Carina; Reuter, Sandra; Wille, Julia; Xanthopoulou, Kyriaki; Stefanik, Danuta; Grundmann, Hajo; Higgins, Paul G.; Seifert, Harald (mBio, 2023)
To give an update on the molecular epidemiology and global distribution of carbapenemase encoding genes, we subjected 313 carbapenem-resistant Acinetobacter baumannii isolated from 114 study centers in 47 countries in five world regions, Africa, Asia, Europe, Latin America, and North America, to whole genome sequencing. Numbers of isolates investigated were proportional to the population size of the contributing countries. Molecular epidemiology was investigated using seven-loci and core genome multilocus sequence typing, whole-genome single nucleotide polymorphism phylogenies, and the intrinsic bla OXA-51-like variant. Carbapenemase encoding genes were identified by multiplex PCR and ResFinder. Among the total of 313 isolates, 289 (92.3%) were assigned to A. baumannii international clones (IC) IC1–IC8. IC2 predominated with 196 isolates (62.6%) and was spread worldwide, followed by IC5 with 44 isolates (14.1%) mainly confined to Latin America. Six isolates (1.9%) originating from Belgium, Egypt, Italy, and Pakistan represent the novel IC9. Acquired OXA-type carbapenemase genes were found in 300 (96%) isolates with bla OXA-23-like and bla OXA-40-like predominating, which constitutes a significant increase compared to our findings from 2010. Metallo-beta-lactamases were rare with seven isolates (2.2%). The distribution of ICs and carbapenemase determinants can vary widely among different geographical regions. Carbapenem-resistant Acinetobacter baumannii are of increasing public health importance, as they are resistant to last-line antibiotics. International clones with well-characterized resistance genes dominate globally; however, locally, other lineages with different properties may be of importance to consider. This study investigated isolates from a broad geographic origin from 114 hospitals in 47 countries and from five world regions ensuring the greatest possible diversity in an organism known for its propensity for clonal epidemic spread and reflecting the current global epidemiology of carbapenem-resistant A. baumannii . In Latin America, a lineage different from other geographic regions circulates, with a different resistance gene profile. This knowledge is important to adjust local infection prevention measures. In a global world with migration and increasing use of antimicrobials, multidrug-resistant bacteria will continue to adapt and challenge our healthcare systems worldwide.